Ensuring the security and privacy of information in mobile health-care communication systems - Ademola Adesina; Kehinde Agbele; Ronald Februarie; Ademola Abidoye; Henry Nyongesa (South African Journal of Science, 2011)
The sensitivity of health-care information and its accessibility via the Internet and mobile technology systems is a cause for concern in these modern times. The privacy, integrity and confidentiality of a patient's data are key factors to be considered in the transmission of medical information for use by authorised health-care personnel. Mobile communication has enabled medical consultancy, treatment, drug administration and the provision of laboratory results to take place outside the hospital. With the implementation of electronic patient records and the Internet and Intranets, medical information sharing amongst relevant health-care providers was made possible. But the vital issue in this method of information sharing is security: the patient's privacy, as well as the confidentiality and integrity of the health-care information system, should not be compromised. We examine various ways of ensuring the security and privacy of a patient's electronic medical information in order to ensure the integrity and confidentiality of the information.